(untitled) (Acta Entomologica Serbica, 2015)
Bagous binodulus (Herbst, 1795) was recorded in Serbia for the first time. Several specimens were collected in the Zasavica Special reserve near Sremska Mitrovica. The general information on this weevil species, including remarks about their distribution in Serbia, is given. Also, we provide the list of Bagous species of the Serbian fauna.